Decision-making under uncertainty in obsessive–compulsive disorder. (October 2015) - Pushkarskaya, Helen; Tolin, David; Ruderman, Lital; Kirshenbaum, Ariel; Kelly, J. MacLaren; Pittenger, Christopher; Levy, Ifat
Abstract: Obsessive compulsive disorder (OCD) produces profound morbidity. Difficulties with decision-making and intolerance of uncertainty are prominent clinical features in many patients. The nature and etiology of these deficits are poorly understood. We used a well-validated choice task, grounded in behavioral economic theory, to investigate differences in valuation and value-based choice during decision making under uncertainty in 20 unmedicated participants with OCD and 20 matched healthy controls. Participants' choices were used to assess individual decision-making characteristics. OCD participants did not differ from healthy controls in how they valued uncertain options when outcome probabilities were known ( risk ) but were more likely than healthy controls to avoid uncertain options when these probabilities were imprecisely specified ( ambiguity ). Compared to healthy controls, individuals with OCD were less consistent in their choices and less able to identify options that should be clearly preferable. These abnormalities correlated with symptom severity. These results suggest that value-based choices during decision-making are abnormal in OCD. Individuals with OCD show elevated intolerance of uncertainty, but only when outcome probabilities are themselves uncertain. Future research focused on the neural valuation network, which is implicated in value-based computations, may provide new neurocognitive insights into the pathophysiology of OCD. Deficits in decision-making processes may represent a target for therapeutic intervention. Graphical abstract: Highlights: We examined differences in valuation and value-based choice under uncertainty in OCD. Compared to controls, individuals with OCD were less consistent in their choices. Compared to controls, individuals with OCD were less able to identify unambiguously preferable options. These difficulties in decision making correlated with OCD symptom severity. OCD participants did not differ from controls in risk aversion, but were more ambiguity averse.